2014
DOI: 10.3390/ijms151119777
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Derivatives NVX-207 and B10 for Treatment of Glioblastoma—An in Vitro Study of Cytotoxicity and Radiosensitization

Abstract: Betulinic acid (BA), a pentacyclic triterpene, represents a new therapeutic substance that has potential benefits for treating glioblastoma. Recently, new strategies for producing BA derivatives with improved properties have evolved. However, few studies have examined the combination of BA or BA derivatives using radiotherapy. The effects of two BA derivatives, NVX-207 and B10, on cellular and radiobiological behavior were analyzed using glioblastoma cell lines (U251MG, U343MG and LN229). Based on IC50 values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Bache et al used BetA at a concentration of 10 µM and demonstrated that radiosensitization ability of BetA could be enhanced in hypoxic condition (51); our study agreed with theirs, while whether Sp1/PTEN pathway involves in hypoxic-induced radiosensitization ability enhancement of BetA is still unknown. Furthermore, there are also several mechanisms reveled underlying BetA-induced radiosensitization (50,51,59). However, our funding could be another important mechanism underlying the BetA enhancement of radiosensitization besides the other previously reported mechanisms (50,51,59), and further supported the assumption that BetA could be a clinically available and promising enhancer of tumor radiotherapy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Bache et al used BetA at a concentration of 10 µM and demonstrated that radiosensitization ability of BetA could be enhanced in hypoxic condition (51); our study agreed with theirs, while whether Sp1/PTEN pathway involves in hypoxic-induced radiosensitization ability enhancement of BetA is still unknown. Furthermore, there are also several mechanisms reveled underlying BetA-induced radiosensitization (50,51,59). However, our funding could be another important mechanism underlying the BetA enhancement of radiosensitization besides the other previously reported mechanisms (50,51,59), and further supported the assumption that BetA could be a clinically available and promising enhancer of tumor radiotherapy.…”
Section: Discussionsupporting
confidence: 86%
“…2C-E). Actually, this concentration of BetA was used also by some other teams in the study of BetA inducing radiosensitization (50,51). Therefore, we chose the concentration of 10 µM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in Figure 1: betulin has three most prominent positions where chemical modifications can be easily accomplished, namely primary hydroxyl group at position C-28, secondary hydroxyl group at position C-3, and alkene moiety at position C-20.The bio-chemical modifications at positions C-28 of the parent structure of betulin produces betulinic acid [12,27,[38][39][40][41]. The chief source of Betulin is bark of Birch trees, belonging to family Betulaceae the family of flowering plants.…”
Section: Occurrence Of Betulin In Naturementioning
confidence: 99%
“…The bio-chemical modifications at positions C-28 of the parent structure of betulin can produce betulinic acid (Fig. 1b) (Yogeeswari and Sriram 2005;Csuk et al 2006;Baratto et al 2013;Bache et al 2014;Csuk 2014). Betulinic acid is commercially produced via chemical synthesis where betulin is used as raw material (Csuk et al 2006).…”
Section: Introductionmentioning
confidence: 99%